Improved survival with postoperative radiotherapy in thymic carcinoma: A propensity-matched analysis of Surveillance, Epidemiology, and End Results (SEER) database. (June 2017) - Lim, Yu Jin; Song, Changhoon; Kim, Jae-Sung
Highlights: Prognostic impacts of PORT in thymic carcinoma were evaluated using SEER database. Improved survival with PORT was observed in the propensity-matched population. Exploratory subgroup analysis suggested subgroups with potential benefits of PORT. Abstract: Objectives: Thymic carcinoma is a rare and aggressive malignancy with poor prognosis. Although postoperative radiotherapy (PORT) is used for obtaining better locoregional tumor control, its association with survival has not been established. This study evaluated the prognostic impact of PORT in thymic carcinoma. Materials and methods: We identified patients diagnosed with thymic carcinoma between 2004 and 2013 using the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching with Kaplan-Meier and Cox-regression analyses were used to assess prognosis. Results: In the unmatched population (n = 312), 184 (59%) patients underwent PORT. The 5-year overall survival rates were better with receipt of PORT, both before and after matching ( P = 0.012 and 0.007, respectively). After adjusting for related covariates (n = 256), age ≥63 years ( P = 0.023), Masaoka stage III ( P = 0.028) and IV ( P < 0.001), debulking surgery ( P = 0.021), and no receipt of PORT ( P = 0.013) were independently poor prognostic factors. In subgroup analyses, favorable survival impacts of PORT were observed for Masaoka stage III tumors (hazard ratio [HR] 0.31, 95% confidence interval [CI] 0.15–0.66), tumors sized >6.0 cm (HR 0.48, 95% CI 0.26–0.89), node-negative status (HR 0.58, 95% CI 0.33–1.00), and surgical extent of local excision or partial removal (HR 0.44, 95% CI 0.22–0.86). Conclusion: On SEER analysis, survival benefits of PORT in thymic carcinoma were demonstrated. With strong prognostic associations of Masaoka stage and types of surgery, PORT should be considered for non-metastatic locally advanced tumors with limited surgical resection.